Pengaruh Gerakan Sadar Halal dan Pengetahuan Produk Pada Gaya Hidup Halal Terhadap Keputusan Pembelian Gen Z - Azizah, Qurrotul; Dzikrulloh, Dzikrulloh (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
Further research is needed given the inconsistencies to test and confirm the findings of previous research results and to get answers to the influence of new variables is the purpose of this research. Online questionnaires were distributed as part of the quantitative methodology of this study. Purposive sampling was the method used to draw the sample. 100 respondents participated in filling out the questionnaire distributed in East Java. For data processing, structural equation modeling, or SEM, was adopted. The structural model test (outer model) is the analysis test that is employed. It includes convergent validity, the Average Variance Extracted (AVE) value, discriminant validity, a reliability test, and an inner model that includes direct effect and indirect effect hypothesis testing. The research findings show that the halal conscious movement positively and significantly influences purchasing decisions, both directly with p-values of 0.000 ≥ 0.050 and indirectly with p-values of 0.014 ≥ 0.050. Product knowledge positively and significantly influences purchasing decisions, both directly with a p-value of 0.013 ≥ 0.050 and indirectly with a p-value of 0.014 ≥ 0.050. In addition, the halal lifestyle with p-values of 0.001 ≥ 0.050 positively and significantly influences purchasing decisions, while for the halal conscious movement with p-values of 0.000 ≥ 0.050 and product knowledge with p-values of 0.000 ≥ 0.050 also positively and significantly influences the halal lifestyle.